A comparative study between methylprednisolone versus dexamethasone as an initial anti-inflammatory treatment of moderate COVID-19 pneumonia: an open-label randomized controlled trial - Jakkrit Laikitmongkhon; Tanapat Tassaneyasin; Yuda Sutherasan; Angsana Phuphuakrat; Sirawat Srichatrapimuk; Tananchai Petnak; Dararat Eksombatchai; Kanin Thammavaranucupt; Somnuek Sungkanuparph (BMC Pulmonary Medicine)
Abstract Background The most appropriate anti-inflammatory treatment for moderate COVID-19 pneumonia remains uncertain. We aimed to compare the effectiveness of a high-dose methylprednisolone versus a high-dose dexamethasone in hospitalized moderate COVID-19 pneumonia, regarding the WHO clinical progression scales, mortality, and the length of hospitalization. Methods In this open-labeled randomized controlled trial, we enrolled patients with age > 18 years old who were diagnosed moderate COVID-19 pneumonia confirmed by real-time PCR, evidence of pneumonia by chest imaging and resting oxygen saturation between 90 and 94%. Patients were randomized at a 1:1 ratio to receive methylprednisolone 250 mg/day or dexamethasone 20 mg/day over the first three days. Then the patients in both groups received dexamethasone 20 mg/day on days 4–5, and 10 mg/day on days 6–10. Primary outcome was assessed by a 10-point WHO clinical progression scales ranging from uninfected (point 0) to death (point 10) on the fifth day of treatment. Secondary outcomes including 90-day mortality, length of hospitalization, rate of intensive care unit (ICU) transfer and complications were determined. Results Of 98 eligible patients, the mean age was 76.0 ± 13.3 years. The median date of illness at the time of randomization was 3 days (interquartile range 2, 5). Baseline clinical characteristics and severity did not differ between groups. The WHO clinical progression scales were similar between methylprednisolone and dexamethasone group at 5 and 10 days of treatment [4.84, (95% confidence interval(CI), 4.35–5.33) vs. 4.76 (95% CI, 4.27–5.25), p = 0.821 and 4.32 (95% CI, 3.83–4.81) vs. 3.80 (95% CI, 3.31–4.29), p = 0.140, respectively)]. Both groups did not differ in-hospital mortality, length of hospitalization, and rate of ICU transfer. There were also no differences in steroid-related complications between groups until 90 days of follow-up. Conclusions In patients with moderate COVID-19 pneumonia, initial anti-inflammatory treatment with 250 mg/day of methylprednisolone for three days does not yield better outcomes over high-dose dexamethasone. Trial registration This study was registered at Thai Clinical Trials Registry on October 17, 2021, with the identifier TCTR20211017001.